COGNITION ENGAGEMENT OF 8TH CLASS STUDENTS IN SCIENCE LEARNING - S. SUCHIRITHA DEVI, B. SPANDANA, P. AMALAKUMARI, R. NEELA RANI AND (The Journal of Research, PJTSAU, 2019)
Cognition engagement was endorsed by the educational psychologists as a major part of overall learning engagement. It indicates the effectiveness of the stimulus that created an environment to the learner to immerse into it. It is rather an in-depth reflective learning process that is situated in realistic problemsolving tasks. Cognition Engagement is defined as a form of instruction that challenges students to draw upon basic skills to engage in higher level thinking. According to Ge and Ifenthaler (2017) it is to engaging in effortful tasks with purposiveness and strategy use, making cognitive investment in learning, and engaging in metacognition and self-regulated learning.Chan and Bose (2016) Student’s cognitive effort is invested to learn, understand, and master the intended knowledge and skills.In the present study it was operatonalised as the achievement of the learner in answering the questions of higher level thinking order.